2022
DOI: 10.3390/cancers14061401
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded Protein Response Is Activated by Aurora Kinase A in Esophageal Adenocarcinoma

Abstract: Unfolded protein response (UPR) protects malignant cells from endoplasmic reticulum stress-induced apoptosis. We report that Aurora kinase A (AURKA) promotes cancer cell survival by activating UPR in esophageal adenocarcinoma (EAC). A strong positive correlation between AURKA and binding immunoglobulin protein (BIP) mRNA expression levels was found in EACs. The in vitro assays indicated that AURKA promoted IRE1α protein phosphorylation, activating prosurvival UPR in FLO-1 and OE33 cells. The use of acidic bile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Additionally, Lu H et al. conducted an investigation into AURKA’s function in EAC ( 19 ). Their analysis of AURKA expression and binding immunoglobulin protein (BIP) in EAC revealed a positive correlation between AURKA and a cellular phenomenon known as the unfolded protein response (UPR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Lu H et al. conducted an investigation into AURKA’s function in EAC ( 19 ). Their analysis of AURKA expression and binding immunoglobulin protein (BIP) in EAC revealed a positive correlation between AURKA and a cellular phenomenon known as the unfolded protein response (UPR).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, their study lacks experimental validation. Additionally, in ESCA, most studies have concentrated on AURKA’s role in esophageal squamous cell carcinoma, with limited attention given to EAC ( 6 , 18 , 19 ). Particularly, there is a paucity of literature that comprehensively synthesizes the clinical significance and molecular biological functions of AURKA in EAC and other malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed the activating and facilitating role of ERS and its downstream responses in EC: Lu H et al (2022) found that aurora kinase A (AURKA), a mitotic kinases mediating several protumor genic functions, promotes UPR through IRE1 phosphorylation in vitro and in vivo , resulting in adaptive survival of EAC cells FLO-1, LO33 and SK-GT4. Chen SM et al (2023) found that Fusobacterium nucleatum (Fn)-induced ERS-related proteins GRP78 and XBP1 high expression could promote the malignant evolution of KYSE150 and KYSE140 in ESSC cells.…”
Section: Dual Effect Of Ers In Digestive System Tumorsmentioning
confidence: 95%
“…CD44, a commonly upregulated protein in EAC [95], also has direct protein interactions with ABCB1, ABCC1, SLC2A1, SLC7A11 and SLC9A1. All transporters, except for SLC6A20, have either direct or indirect interactions with key regulatory proteins previously reported in EAC, including the transcription factors ATF4 and NFκB, unfolded protein response-related proteins (ERN1 or IRE1, ATF4) and multiple inflammation, bacterial and immune-linked proteins (i.e., PTGS2/Cox2, MYD88, IL-8 or CXCL8, IL-1β, CD44) [96][97][98][99]. The string network further illustrates the connectivity between families of transporters (ABCs and SLCs).…”
Section: Transporter Dysregulation Observed In Human Esophageal Cance...mentioning
confidence: 99%